Clinicopathological Analysis of Glomerular Disease of Adult Onset Nephrotic Syndrome in an Indian Cohort- A Retrospective Study - Suryawanshi, Mayur (J Clin Diagn Res, 2017)
INTRODUCTION: Primary glomerular disease presenting with adult onset nephrotic syndrome are a major cause of chronic renal failure worldwide. The spectrum of renal disease presenting with nephrotic syndrome has undergone a gradual change globally over the course of time. However, there still exist regional differences in the incidence of primary glomerular diseases causing adult onset nephrotic syndrome. AIM: To observe the spectrum of renal diseases presenting with adult onset nephrotic syndrome with comparative analysis of changing trends over the last five decades with regards to Western and Indian literature. MATERIALS AND METHODS: Subjects included patients with age of 18-80 years presenting with nephrotic syndrome. Renal biopsies with immunofluoroscence studies were performed in all patients. Baseline clinical parameters of serum urea, creatinine, albumin, globulin, cholesterol, 24 hour urine protein and urine microscopy were recorded. Descriptive statistics was used and results were expressed as frequencies, percentages, and mean±standard deviation. RESULTS: A total of 227 patients (72% males) were included for the study. Primary glomerular diseases formed 74.01% of total cases and majority of patients included males in the 4(th) decade. Minimal Change Disease (MCD) (15.8%) including its variants was the most common primary glomerular disease for adult onset of nephrotic syndrome followed by Mesangial proliferative Glomerulonephritis (MSGN) (13.2%). Membranous nephropathy and Type I Membranoproliferative Glomerulonephritis (MPGN) individually accounted for 12.3% of patients. Focal and Segmental Glomerulosclerosis (FSGS) accounted for only 11% of patients. Although, increased incidence of FSGS has been observed worldwide, there exist important regional differences in primary glomerular diseases in Indian population. MCD remains a major glomerular disease for adult onset nephrotic syndrome in different parts of India. CONCLUSION: Our study over three years represents important data of regional variations of primary glomerular diseases presenting with adult onset nephrotic syndrome.